Effect of different mounting angles of prosthetic feet dedicated to sprinting on reaction forces - Litzenberger, S.; Sabo, A.; Fuss, F. K. (Procedia Engineering, 2016)
Prosthetic sprinting feet made of carbon fibre reinforced plastics for transtibial amputee athletes are widely used by hobby athletes and in professional competition. However, so far work done to assess static and dynamic properties of prosthetic feet dedicated to sprinting did not take into account different mounting angles of the prostheses onto the shaft. In this research two sprint prostheses (Otto Bock Sprinter feet) with low (P1) and mid stiffness (P3), used for athletes of high activity level in Paralympic sports were subjected to compressive loads on a motor driven static test bench under quasi-static loading conditions at different mounting angles (0, 5 and 18 degrees) and vertical and horizontal reaction forces were measured. The energy return did not show unambiguous dependence on mounting angles. The results showed that both vertical and horizontal stiffness decreased as the mounting angle increased, which was unexpected and requires further examination.